Enhancing self-efficacy through a blended training: A pilot study with basketball players - Villani, D.; Caputo, M.; Balzarotti, S.; Riva, G. (International Journal of Sport and Exercise Psychology, 2017)
In the last decade, research has shown that web-based technology can be effectively employed to support interventions aimed at the empowerment of psychological skills such as self-efficacy. In this study, we tested the effectiveness of an innovative blended training program combining face to face and web-based activities in enhancing self-efficacy and emotion regulation among young basketball players. The training program lasted seven weeks and was based on the four sources of self-efficacy information identified by Bandura. In a two-group pre-test and a post-test design, 37 basketball players received either a web-based or a control text-based training program. The results indicated that the athletes receiving the web-based interactive training reported higher levels of self-efficacy compared to the baseline assessment, while no significant differences emerged in the control group. Concerning emotion regulation, both groups reported less emotional suppression at the end of the training, while no significances emerged for cognitive reappraisal. However, cognitive reappraisal was associated with self-efficacy as measured before and after the intervention. These findings seem to suggest that blended training programs may be a promising approach to promote self-efficacy in sport.